2020
DOI: 10.1029/2019ms001754
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Blending Scheme to Mitigate Large‐Scale Bias in Regional Models

Abstract: Several blending methods have been developed in dynamic downscaling and rapid cycled data assimilation. Blending the large‐scale part of the global model (GM) analysis or forecast has led to improvement in regional model (RM) simulations. However, in previous studies the blended waveband of the GM has generally been determined using a fixed, arbitrarily chosen cutoff wave number. Here we introduce a new dynamic blending (DB) scheme with a dynamic cutoff wave number computed according to the spectral characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…As in other work (e.g., Wang et al ., 2014; Feng et al ., 2020), we adopt the sixth‐order implicit tangent filter described by Raymond (1988; referred to as the Raymond filter hereafter), which is particularly suitable for use in limited‐area models. At a given wavenumber k$$ k $$, the amplitude response of the Raymond filter is trueα^false(kfalse)=[]1+ϵtan6()knormalΔ2prefix−1,$$ \hat{\alpha}(k)={\left[1+\epsilon {\tan}^6\left(\frac{k\Delta}{2}\right)\right]}^{-1}, $$ where ϵ=tanprefix−6()knormalcnormalΔ2,$$ \epsilon ={\tan}^{-6}\left(\frac{k_{\mathrm{c}}\Delta}{2}\right), $$ normalΔ$$ \Delta $$ is the model grid spacing, and knormalc$$ {k}_{\mathrm{c}} $$ is a characteristic wavenumber at which the Raymond filter possesses half power, trueα^false(knormalcfalse)=0.5$$ \hat{\alpha}\left({k}_{\mathrm{c}}\right)=0.5 $$.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other work (e.g., Wang et al ., 2014; Feng et al ., 2020), we adopt the sixth‐order implicit tangent filter described by Raymond (1988; referred to as the Raymond filter hereafter), which is particularly suitable for use in limited‐area models. At a given wavenumber k$$ k $$, the amplitude response of the Raymond filter is trueα^false(kfalse)=[]1+ϵtan6()knormalΔ2prefix−1,$$ \hat{\alpha}(k)={\left[1+\epsilon {\tan}^6\left(\frac{k\Delta}{2}\right)\right]}^{-1}, $$ where ϵ=tanprefix−6()knormalcnormalΔ2,$$ \epsilon ={\tan}^{-6}\left(\frac{k_{\mathrm{c}}\Delta}{2}\right), $$ normalΔ$$ \Delta $$ is the model grid spacing, and knormalc$$ {k}_{\mathrm{c}} $$ is a characteristic wavenumber at which the Raymond filter possesses half power, trueα^false(knormalcfalse)=0.5$$ \hat{\alpha}\left({k}_{\mathrm{c}}\right)=0.5 $$.…”
Section: Methodsmentioning
confidence: 99%
“…As in other work (e.g., Wang et al, 2014;Feng et al, 2020), we adopt the sixth-order implicit tangent filter described by Raymond (1988; referred to as the Raymond filter hereafter), which is particularly suitable for use in limited-area models. At a given wavenumber k, the amplitude response of the Raymond filter is…”
Section: Generation Of Incrementsmentioning
confidence: 99%
“…Negative biases occur in a few windy mountainous areas of Xinjiang, northern Inner Mongolia, and the Qinghai-Tibet Plateau (Lew, 2000). Previous studies have reported similar SWS prediction errors in other regions (Duan et al, 2018;Feng, Sun, & Zhang, 2020;Misaki et al, 2019;Pan et al, 2021;Shimada et al, 2011;Wyszogrodzki et al, 2013).…”
mentioning
confidence: 70%
“…Despite the inconsistent x b and K, background blending has been demonstrated to significantly improve the forecast quality in different parts of the world [5,12,15,16]. This suggests that the errors due to incorrect large-scale information in LAMs are perhaps more significant than the errors due to the aforementioned inconsistency.…”
Section: Background Blendingmentioning
confidence: 99%